A Colônia Militar São Pedro de Alcântara no Rio Gurupi e a redefinição da fronteira Pará-Maranhão (1852-1873) - ROSÁRIO, Talita Almeida do (2021)
The settlement of the military colony “São Pedro de Alcântara” demarcated on the Gurupi river in the year 1854, on the Pará-Maranhão border, met the demands of the Maranhão Province for investments in the Gurupi-Turiaçu region, which had been recently incorporated to its territory. Therefore, the hybrid nature of the colony being military and agricultural was related to the dominance of Maranhão through the advance of land owners and the control of populations that the imperial administration saw as “undesirable subjects”, which traditionally worked the productive lands of the region and felt they owned it. Given the best interests of Maranhão authorities and the rising question about impacts that the colony would bring to the dynamics of the two rivers region and lives of its inhabitants, this research aims at how the different people and ethnic groups understood the creation of the colony. Through the multiple sources and official speeches analyzed was clear the aim to justify their presence, revealing representations about the Turiaçu region and its people. In addition, an ethnic diversity was found in the Gurupi area, which fed relations of conflict, trade and negotiation with the colony. On the other hand, understanding that it was a post of police and civilizational, some groups such as indigenous and poor people built spaces of resistance and refuge in that same river.